Policing by Injunction: Problem-Oriented Dimensions of Civil Gang Abatement in the State of California, 1987-2001 - Allan, Edward L. ([Verlag nicht ermittelbar], 2003)
This study examined whether civil gang abatement is consistent with the model of problem-oriented intervention. Civil gang abatement is a legal strategy that employs the civil remedy of the preventive injunction to address persistent public nuisances caused by gangs in specific neighborhoods. This study focused on injunction initiatives, which are efforts by prosecutors to acquire a preliminary injunction against a gang, regardless of the decision by the court. The researcher examined all identified gang injunction cases filed with the Superior Court of California from October 1987 through June 2001. Data on gang activities that led to efforts to obtain injunctions were gathered from court records, and additional data were gathered through surveys of the prosecutors involved in each injunction initiative. Questions in the survey covered the nature of the gang problem, the entity responsible for initiating the effort to get an injunction, specific events that triggered the initiative and influenced it after initiation, the existence of other interventions or programs conducted in conjunction with the initiative, the prosecutors' perceptions of the nature and impact of community involvement, and information on community entities that supported and opposed the initiatives.